The Crimea Crisis from an International Law Perspective - Marxsen, Christian (Kyiv-Mohyla law & politics journal, 2016)
In February and March 2014, Ukraine was literally overrun by a chain of events that eventually led to Crimea’s incorporation into Russian territory. Crimean and Russian authorities jointly used the internal conflict in Ukraine to deprive the Ukrainian government of its control over Crimea, to hold a so-called referendum, and to declare Crimea’s independence. On the day after independence was declared, Russia formally recognized Crimea as an independent state,[1] and the Crimean parliament requested Russia to admit Crimea to the Russian Federation.[2] Soon after that, the accession treaty was signed, and, within a few more days, all Russian constitutional requirements for Crimea’s accession to the Russian Federation were fulfilled.[3]All parties to the conflict refer to international law to justify their positions. The Crimean authorities and Russia claim that Russia had a legal basis for intervening and that Crimea had the right to secede from Ukraine. Most states, however, reject these claims. Thus, three questions are presented: Was Crimea’s secession lawful under international law? To what extent has Russia violated international law? And what is Crimea’s status? This article addresses these questions. Part 1 briefly describes the relevant circumstances and events leading to Crimea’s secession. Part 2 reviews the legal obligations between Ukraine and Russia concerning territorial integrity and the prohibition against the use and threat of force. Parts 3 and 4 discuss the legality of Russia’s intervention in Crimea and the legality of Crimea’s secession from Ukraine, respectively. Part 5 concludes this article by answering the questions it raises. [1] See “Executive Order on Recognizing Republic of Crimea,” President’s web-site, March 17, 2014, accessed June 1, 2016, http://en.kremlin.ru/events/president/news/20596. [2] Luke Harding and Shaun Walker, “Crimea Applies to be Part of Russian Federation After Vote to Leave Ukraine,” The Guardian, March 17, 2014, accessed June 1, 2016, http://www.theguardian.com/world/2014/mar/17/ukraine-crimea-russia-referendum-complain-result. [3] See in regard to the Russian constitutional process Otto Luchterhandt, who argues that during that process Russian constitutional law was violated (Otto Luchterhandt, “Annexion der Krim – Putin verstößt gegen russische Verfassung,” Frankfurter Allgemeine Zeitung, April 18, 2014).